ORIENTASI KEWIRAUSAHAAN, ORIENTASI PASAR, DAN STRATEGI BISNIS TERHADAP KINERJA BISNIS (Studi kasus pada UMKM di Semarang) - Rahmi Yuliana; Yanti Pujiastuti (FEB Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this research is to examine the effect of entrepreneurship orientation, market orientation and business strategy on business performance. The study was conducted on MSMEs registered in the Office of Cooperatives of Semarang City consisting of bags, batik and handicraft business. Sampling using purposive sampling and got 51 samples. The data collected through the questionnaire were analyzed by regression technique.The test results found that entrepreneurial orientation,market orientation and business strategy partially have a positive and significant impact on business performance. Simultaneous testing shows that entrepreneurial orientation,market orientation and business strategy together have a significant effect on business performance.Increased entrepreneurial orientation, market orientation and business strategies can be done to improve business performance because it has proven to have a significant positive effect on business performance.keyword: entrepreneurship orientation, market orientation, business strategy and business performance